2015
DOI: 10.1002/2015je004863
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative compositional analysis of sedimentary materials using thermal emission spectroscopy: 1. Application to sedimentary rocks

Abstract: Thermal emission spectroscopy is used to determine the mineralogy of sandstone and mudstone rocks as part of an investigation of linear spectral mixing between sedimentary constituent phases. With widespread occurrences of sedimentary rocks on the surface of Mars, critical examination of the accuracy associated with quantitative models of mineral abundances derived from thermal emission spectra of sedimentary materials is necessary. Although thermal emission spectroscopy has been previously proven to be a viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 72 publications
(142 reference statements)
1
21
1
Order By: Relevance
“…Figure compares NNLS‐derived mineral abundances with PLS‐derived abundances to that of XRD abundances for the mudstone samples from paper 1 [ Thorpe et al , ]. The PLS method retrieved known abundances to within ±10% for the majority of the mudstones, with no more than three samples falling outside this range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure compares NNLS‐derived mineral abundances with PLS‐derived abundances to that of XRD abundances for the mudstone samples from paper 1 [ Thorpe et al , ]. The PLS method retrieved known abundances to within ±10% for the majority of the mudstones, with no more than three samples falling outside this range.…”
Section: Resultsmentioning
confidence: 99%
“…Mineral abundance is determined by full pattern X‐ray diffraction quantitative refinements from Thorpe et al [].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we modeled the spectra with a set of 19 laboratory spectra using a nonnegative linear least squares minimization routine (Lawson & Hanson, ; Rogers & Aharonson, ). For thermal emission spectra of rocks and coarse particulates (>~60 μm), and using a library that captures the range of minerals present in the mixture, this technique is capable of retrieving areal mineral abundances to within 15% absolute accuracy (Feely & Christensen, ; Hamilton & Christensen, ; Ramsey & Christensen, ; Thorpe et al, ). Mineral detection limits depend on the mixture but generally range between ~5 and 15% (Christensen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 1,000-particle clusters preserve the balance between improvements in modeled spectra and the increasing computational burden with the use of more particles. We investigate midinfrared wavelengths in this work as the analytical methods for this wavelength range require substantial improvement when analyzing spectra of fine-grained regolith surfaces (e.g., Ramsey & Christensen, 1998;Rogers et al, 2007;Thorpe et al, 2015). Ito et al (2017) observed that the use of the superposition T-matrix method to compute the single-scattering characteristics of an elementary volume results in a spurious forward-scattering feature, wherein the magnification of the "diffraction" peak caused by the far-field effect of forward-scattering interference (Mishchenko, Figure 1.…”
Section: Elementary-volume Scattering Parameter Computationmentioning
confidence: 99%